2022
DOI: 10.3390/ijms23052748
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Targeted Metabolomic Study in the Lung, Plasma, and Urine of PPE/LPS-Induced COPD Mice Model

Abstract: (1) Background: Progression of chronic obstructive pulmonary disease (COPD) leads to irreversible lung damage and inflammatory responses; however, biomarker discovery for monitoring of COPD progression remains challenging. (2) Methods: This study evaluated the metabolic mechanisms and potential biomarkers of COPD through the integrated analysis and receiver operating characteristic (ROC) analysis of metabolic changes in lung, plasma, and urine, and changes in morphological characteristics and pulmonary functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Animal models of COPD such as generated by exposure to cigarette smoke (CS) can help better understand the underlying mechanisms of CS induced COPD and study the role of various inflammatory and metabolic pathways ( 12 , 13 ). Although COPD mouse can mimic some of the features of the disease, this model does not fully reflect all of the characteristic features of human disease due to the physiological, genetic and environmental differences between human and mouse ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Animal models of COPD such as generated by exposure to cigarette smoke (CS) can help better understand the underlying mechanisms of CS induced COPD and study the role of various inflammatory and metabolic pathways ( 12 , 13 ). Although COPD mouse can mimic some of the features of the disease, this model does not fully reflect all of the characteristic features of human disease due to the physiological, genetic and environmental differences between human and mouse ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that central carbon metabolism played an essential role in the development of pulmonary diseases. For instance, in the PPE/ LPSinduced chronic obstructive pulmonary disease(COPD) mice model [11]., the differences in urinary succinic acid, isocitric acid, and pyruvic acid were statistically significant [11]. Another bleomycin model of pulmonary fibrosis in mice found that increased level of glycolysis, TCA cycle, and PPP associated with upregulated energy production for energy demand of the fibrotic lungs [12].…”
Section: Introductionmentioning
confidence: 99%